Pengaruh Persepsi Pengusaha Kecil Dan Menengah Terhadap Penggunaan Sak Etap Di Kota Bandar Lampung (Studi Pada Sentra Kripik Segalamider Bandar Lampung) - Rosmiaty Tarmizi; Ni Luh Sartika Bugawanti (Jurnal Akuntansi dan Keuangan, 2013)
Accounting practices, financial accounting in particular on SMEs in Indonesia is still low and has many drawbacks. Weakness, partly due to lack of education, lack of understanding of Financial Accounting Standards (GAAP) of the owners and managers in the absence of regulations requiring the preparation of financial statements for SMEs. The main problem in this research is how the influence of perception of small and medium enterprises to the use of SAK ETAP?. The purpose of this study was to determine the effect of the perception of how small and medium enterprises to the use of SAK ETAP ". The hypothesis is the perception of small and medium enterprises to the use of SAK ETAP in Bandar Lampung. From the discussion of the results obtained by the regression equation Y = 22.760 +0.300 X and hypothesis test results using the t test, where the real level tcount df = 54 and Î± = 0.05 at 3.567 significant at p-value 0.001 and the value of TTable (appendix t_tabel ) of 2.005, thus tcount> TTable (3.567> 2.005). Which means that the hypothesis is proven and can be accepted as true.